Correlation between optical coherence tomography angiography-based data and postoperative visual acuity in patients that underwent surgery for macula-on RRD and macula-off RRD - I. Bezkorovaina; A. Ivanchenko (Ukrainian Society of Ophthalmologists, 2023)
Background: Despite advances in surgical techniques for rhegmatogenous retinal detachment (RRD) repair, patients are still at high risk for low functional outcomes. Given the above, it is important to find reasons for disappointment at the outcomes of vitreoretinal surgery for RRD. Impaired retinal microcirculation is a possible cause of insufficiently good functional outcomes in surgery for RRD. Purpose: To compare postoperative optical coherence tomography angiography (OCTA)-based changes in retinal microcirculation in the eyes of patients that underwent surgery for macula-on RRD versus the eyes of patients that underwent surgery for macula-off RRD and (2) to establish a relationship between OCTA data and best-corrected visual acuity (BCVA). Material and Methods: This prospective study included 116 patients. Of these, 65 underwent surgery for macular-on RRD (group 1) and 51, surgery for macular-off RRD (group 2). OCTA-based retinal vasculature parameters (foveal avascular zone (FAZ) area, parafoveal superficial capillary plexus (SCP) density and deep capillary plexus (DCP) density, vessel diameter, and vessel tortuosity index (VTI)) and their correlation with BCVA were assessed. Follow-up duration was 12 months. Results: In group 1, there was a negative correlation between the FAZ area and the macular thickness (r = - 0.299, p = 0.025) at month 12. The final BCVA was associated with the parafoveal DCP density (r = - 0.340, p = 0.010) and FAZ area (r= 0.390, p = 0.003). At 12 months, in group 2, the BCVA negatively correlated with the FAZ area (r = - 0.408, p = 0.012) and parafoveal SCP density (r = - 0.451, p = 0.005). In addition, there was a negative correlation between the parafoveal DCP density and the postoperative BCVA (r = - 0.418). There was no correlation between the FAZ area and the macular thickness (r = - 0.282, p = 0.080). Conclusion: The poorer vessel tortuosity index and parafoveal vessel density and diameter, the lower was postoperative visual acuity.